Toward A Typology of Circular Economy Agency - Teerikangas Satu; Onkila Tiina; Koistinen Katariina; Hirvensalo Antero; Korsunova Angelina; Mäkelä Marileena; Sarja Milla; Valkjärvi Mira; Reynolds Noelia-Sarah (Routledge, 2025)
Agency, in its many forms, is identified as a critical factor enabling sustainability transitions. All the while, the role of agency vis-à-vis the CE transition remains poorly recognised. This chapter explores the agency of individuals and organisations driving the circular transition. The research approach used in this chapter is abductive, building upon the interdisciplinary research team's theoretical and empirical insights in the study of CE agency in 2015–2022. This chapter 1) introduces the concept of CE agency and 2) develops a typology of CE actors and their active and relational agency at the individual, organisational, and inter-organisational levels of analysis. Theoretically, this chapter finds that the struggles experienced by active CE actors are embedded in an ongoing negotiation between agency and the surrounding structures; and therefore, views circular transitions as structuration processes amid an ongoing tension between agency and structure. Where agency is active and relational, it bears the potential to shift prevailing linear-economy-biased structures toward circularity. In closing, the researchers argue that all actors have the potential to become CE catalysts, depending on the extent to which they recognise and exercise their CE agency.
The Routledge Handbook of Catalysts for a Sustainable Circular Economy